Front Cover: Colloidosomes as a Protocell Model: Engineering Life‐Like Behaviour through Organic Chemistry (Eur. J. Org. Chem. 6/2023). Issue 6 (31st January 2023) - Park, Jun Hyeong; Galanti, Agostino; Ayling, India; Rochat, Sebastien; Workentin, Mark S.; Gobbo, Pierangelo
Abstract : The Front Cover illustrates an adapted brightfield microscopy image of colloidosome protocells produced from gold nanoparticles using the Pickering emulsions technique. The artwork highlights the role of organic chemistry in the engineering of colloidosomes with life‐like behaviors, which is the subject of this review article. Cover designed by Jun Hyeong Park and Dr. Pierangelo Gobbo. More information can be found in the Review by P. Gobbo et al .